1997
DOI: 10.1002/hep.510260320
|View full text |Cite
|
Sign up to set email alerts
|

The effects of N -acetylcysteine and anti-intercellular adhesion molecule-1 monoclonal antibody against ischemia-reperfusion injury of the rat steatotic liver produced by a choline-methionine-deficient diet

Abstract: tory injury is involved in hypothermic I/R injury, that oxidaAbundant fat in the liver has been implicated in poor outtive stress produced by PMNLs is involved in normothermic come after liver transplantation or liver surgery, but the rea-I/R injury, and that NAC and anti-rat ICAM-1 monoclonal sons for this association are still unclear. The aim of the antibody restore liver integrity in I/R injury. (HEPATOLOGY present study was to examine mechanisms that may be in-1997;26:670-678.) volved in hepatic dysfuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 9 publications
1
20
0
Order By: Relevance
“…A previous study similarly observed a significant reduction in the level of GSH in steatotic livers induced by a choline-methionine-deficient diet compared with that in normal livers (28). Low GSH levels may underlie the greater susceptibility of steatotic livers to reperfusion injury.…”
Section: Bucillamine Greatly Enhances Gsh Levels and Blocks The Formamentioning
confidence: 72%
See 1 more Smart Citation
“…A previous study similarly observed a significant reduction in the level of GSH in steatotic livers induced by a choline-methionine-deficient diet compared with that in normal livers (28). Low GSH levels may underlie the greater susceptibility of steatotic livers to reperfusion injury.…”
Section: Bucillamine Greatly Enhances Gsh Levels and Blocks The Formamentioning
confidence: 72%
“…The antioxidant enzyme superoxide dismutase had variable effectiveness in previous studies and has been most impressive when administered by gene therapy with viral vectors, an as-yet-unproven technology (12). N-acetylcysteine, especially at high doses, has been successful in preserving microcirculatory function in some studies but has been ineffective in others (28,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). In a pilot clinical study, it also seemed to improve outcomes in patients (46).…”
Section: Discussionmentioning
confidence: 99%
“…In rat liver transplantation, NAC treatment reduced early phase reperfusion injury [5] and decreased leucocyte adherence to sinusoidal endothelium [23]. In a model of hypothermic I/R injury of the steatotic rat liver, NAC given before cold storage for 24 h diminished sinusoidal microcirculatory injury and lowered enzyme release after reperfusion [24]. In an endotoxin sepsis model of the rat, NAC treatment given before as well as after induction of sepsis decreased leucocyte adherence in mesentery vessels and improved haemodynamics [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…1). One study by Nakano et al examined the effect of hepatic steatosis on bioenergetics in both warm and cold IRI [17].…”
Section: Resultsmentioning
confidence: 99%
“…QUORUM Diagram. [18]; b, [19]; c, [20]; d, [21]; e, [22]; f, [23], g, [24]; h, [25]; i, [26]; j, [27]; k, [28]; l, [29]; m, [30]; n, [17]; o, [31]; p, [32]; q, [33]; r, [34]; s, [35]; t, [36]; u, [37] [38]; b, [39]; c, [40]; d, [41]; e, [42]; f, [43]; g, [44]; h, [45]; i, [46]; j, [47]; k, [48]; l, [49]; m, [50]; n, [51]; o, [52] [62]; c, [63]; d, [64]; e, [65]; f, [66]; g, [67]; h, [68]; i, [69]; j, [70]; k, [71]; l, [17]; m, [60]; n, [72]; o, [73]<...>…”
Section: Papers Identified From Reference Lists N=19mentioning
confidence: 99%